Crisis response and management and emerging information systems : critical applications - Jennex, Murray E., 1956- (Hershey, PA : Information Science Reference, 2011)
"This book provides a comprehensive, cross disciplinary look at the advancing and understanding of organizational, technical, human, and cognitive issues associated with the use of information systems in responding and managing crises of all kinds"--Provided by publisher.
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Emergency management -- Information services; Emergency management -- Information technology; Emergency communication systems